Effect of Solvents in Synthesis of New 4-(2 Hydroxy-5-Methylphenyl)-6-Aryl-2-Imino-6H-2,3-Dihydro-1,3-Thiazines - Dighade, S.R.; Chincholkar, M.M. (Asian Journal of Chemistry, 2010)
Seven different chalcones were synthesised from 2-hydroxy-5- methyl acetophenone using two ketones and five aldehydes in alkaline medium. These chalcones I(a)-I(g) on treatment with thiourea in pyridine gave seven 1,3-thiazines lI(a)-II(g). It is also reported that pyridine-KOH gives better yield and shorter duration for reaction completion than pyridine or ethanol-KOH. The structures of these compounds were confirmed on the basis of chemical and spectral analysis.